Systemic administration of TLR3 agonist induces IL-7 expression and IL-7-dependent CXCR3 ligand production in the lung - Jin, Jun-O (Society for Leukocyte Biology, 2013)
In this study, we tested the hypothesis that systemic administration of TLR3 agonist poly I:C can enhance T cell infiltration of lung through up-regulating IL-7 expression. poly I:C, a synthetic analog of viral dsRNA and a TLR3 agonist, is studied extensively as vaccine adjuvant as a result of its pleotropic immune-stimulatory effects. Here, we show that systemic poly I:C administration induces substantial IL-7 production in the lung in a type 1 IFN- and IFN-γ-dependent fashion. Blockade of the IL-7Rα signal with a neutralizing antibody abrogated poly I:C-induced MCP-1 up-regulation, macrophage recruitment, and CXCR3 ligand expression in the lung. Conversely, administration of IL-7 enhances these events, and it does so by enhancing T cell IFN-γ production. We also show that the initial up-regulation of CXCR3 ligands and infiltration of T cells in the lung are mediated by poly I:C-induced IFN-γ from NK cells; however, the sustained and optimal CXCR3 ligand expression and T cell infiltration require poly I:C-induced IL-7 and T cell-derived IFN-γ. In a model of multiorgan inflammation elicited by adoptive transfer of immune cells into RAG1(−/−) mice, we show that poly I:C enhances IL-7 production in the lung and promotes expression of CXCR3 ligands and recruitment of IFN-γ(+) T cells in an IL-7-dependent fashion. Collectively, these results strongly support our hypothesis and delineate a new mechanism by which poly I:C boosts the T cell immune response in the lung by inducing local IL-7 production, which in turn, enhances T cell-derived IFN-γ to promote macrophage recruitment, CXCR3 ligand expression, and T cell infiltration.